2018
DOI: 10.1152/ajpcell.00064.2017
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Parkin impairs mitochondrial function and leads to muscle atrophy

Abstract: Parkinson's disease is a neurodegenerative disease characterized by tremors, muscle stiffness, and muscle weakness. Molecular genetic analysis has confirmed that mutations in PARKIN and PINK1 genes, which play major roles in mitochondrial quality control and mitophagy, are frequently associated with Parkinson's disease. PARKIN is an E3 ubiquitin ligase that translocates to mitochondria during loss of mitochondrial membrane potential to increase mitophagy. Although muscle dysfunction is noted in Parkinson's dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 78 publications
2
46
0
Order By: Relevance
“…In an in vitro study, siRNA‐mediated Parkin knockdown was shown to have considerably diminished protein levels of both MFN1/2 and Drp1 in C2C12 myoblasts (Peker et al . ) for which the initial differentiation process into myotubes requires the upregulation of autophagic proteins (Sin et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an in vitro study, siRNA‐mediated Parkin knockdown was shown to have considerably diminished protein levels of both MFN1/2 and Drp1 in C2C12 myoblasts (Peker et al . ) for which the initial differentiation process into myotubes requires the upregulation of autophagic proteins (Sin et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, impaired Parkin led to dysregulated mitochondrial function, as well as smaller fibre size (Peker et al . ), suggesting that it has an essential role in muscle development. A loss of PINK1 and Parkin has also been recently associated with a strong inflammatory phenotype after exhaustive exercise in mice (Sliter et al .…”
Section: Introductionmentioning
confidence: 99%
“…Pramstaller presented one HPHA female patient with parkin mutations (Pramstaller et al, 2002). Peker found that the knockdown of the Parkin gene led to myotubular atrophy in vitro, an effect that was associated with impaired mitochondrial function and a smaller myofiber area (Peker et al, 2018). Consequently, the genetic etiology of HPHA and HDHA, which include parkin mutations, cannot be fully excluded.…”
Section: Discussionmentioning
confidence: 99%
“…ROS are highly reactive byproducts of mitochondrial respiration and their accumulation will impair cellular components and activate death pathways; however, cells initiate related mechanisms such as mitophagy to opposite ROS accumulation [10] [11] [12]. MMP is another byproduct of OXPHOS, and its reduction can activate PINK1-Parkin pathway to induce mitophagy [13] [14].…”
Section: Discussionmentioning
confidence: 99%